Perencanaan Jaminan Mutu Sekolah Dasar Islam Terpadu - Yuhdi, Yuhdi; Mujahidin, Endin; Andriana, Neisa; Supraha, Wido; Tamam, Abas Mansur (EduInovasi: Journal of Basic Educational Studies, 2024)
The achievement of educational goals is marked by the quality of education. The quality of education is considered good when the national education goals and the goals of Islamic education are achieved. The planning stage is crucial, especially in relation to ensuring the quality of education. This study analyzes the quality assurance planning of the Terpadu Islamic elementary school, especially those within the Integrated Islamic School Network (JSIT) in Indonesia. This research uses a qualitative approach in the form of literature study and observation. The results obtained show that the Ummul Quro Bogor Integrated Islamic Elementary School has carried out quality assurance planning in accordance with national education standards and the standards of the Integrated Islamic School Network (JSIT).